Education and Training as a Tools for Sustainable Development among Secondary School Teachers in Southwest Nigeria - Elijah, Olorunda Sola (Indonesian Journal of Contemporary Education, 2022)
The educational methodologies that might be used to manage education and in-service training among secondary school teachers in southwest Nigeria were mentioned in the paper. The degree of in-service training and academic qualifications of secondary school teachers in Southwest Nigeria were investigated, as well as male and female teachers' impressions of in-service training and re-training by the government. The study employed survey-style descriptive research. In southwest Nigeria, the population was made up entirely of teachers. The study's sample included 200 teachers who were chosen using a multistage sampling approach that included both simple random sampling and stratified random sampling techniques. The study found that secondary school teachers in southwest Nigeria have a low level of in-service training and a high level of academic qualifications and that there is no significant difference in perceptions of in-service training and academic qualifications between male and female secondary school teachers in southwest Nigeria. It was suggested that the government step up their efforts to organize in-service training for secondary school teachers, such as conferences, seminars, and workshops, in order to impart the necessary knowledge to students in order to achieve sustainable development goals. Additionally, necessary types of machinery should be put in place to improve the performance of the ministry of education and local education authorities in order to upgrade teachers and enhance their performance. In conclusion, there is a lack of teacher training and retraining in southwest Nigeria, as well as a high level of academic qualifications among secondary school teachers.